Social Change in the Hidden Kingdom of Nepal's Himalayas : A Case Study of the Baden - Lama, Dipendra (Dhaulagiri Journal of Sociology and Anthropology, 2025)
The rich cultural heritage of Nepal's mountain communities is undergoing rapid transformation, with a noticeable decline in traditional festivals, songs, dances, and cultural practices. These changes pose an ongoing threat to the collective socio-cultural life and history of the people and their homeland, yet this critical issue remains largely under-researched. Focusing on the Baden festivals that were celebrated in Manang village, located in the Nishyang Valley of the Central Himalayas, Nepal, this study aims to elucidate the detailed processes of decline in festival celebration and their relationship to broader social change.The study employs an ethnographic approach, utilizing fieldwork conducted in September-October 2018 and May 2024, which included informal conversations and interviews with local elders, performers, festival organizers, and youths in Manang village. Secondary data, including photos, documentaries, videos, and archives, further supported the analysis. The findings reveal that increasing mobility and out-migration have led to the gradual erosion of indigenous cultural practices, particularly the Baden festival, which once reinforced communal identity and sacred spatial ties. This loss reflects the erosion of the unique cultural heritage of the Nepal Himalayas, with sacred spaces and local traditions under threat as younger generations move away from their ancestral place and customs. By documenting these transformations, the paper calls for a critical rethinking to revitalize and sustain mountain cultural heritage in the face of global and local pressure.